STRATEGI GURU AKIDAH AKHLAK DALAM MENINGKATKAN KARAKTER RELIGIUS PESERTA DIDIK KELAS V MI AL-IKHLAS BUNTU PODONG KABUPATEN ENREKANG - Karmila; Muh. Aidil Sudarmono R; Muhammad Syahrul; Martini; Salim Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the strategies of Akidah Akhlak teachers in developing students' religious character and to identify the supporting and inhibiting factors faced by teachers at MI Al-Ikhlas Buntu Podong, Enrekang Regency. The researchers used qualitative research with a phenomenological approach. Data collection techniques included observation, interviews, and documentation, with data analysis techniques including word reduction, data presentation, and conclusion drawing. The results indicate that teacher strategies are implemented through habituation of religious activities, role models, advice, and direct guidance. These strategies are able to increase students' awareness of worship, politeness, and discipline. Supporting factors include the active role of teachers, student motivation, and a conducive environment. Meanwhile, inhibiting factors include limited infrastructure, particularly ablution facilities, and differences in student character. Thus, teacher strategies play a crucial role in shaping students' religious character and need to be supported by adequate facilities and an environment.